Comparative Evaluation Of Efficacy Pertaining To Different Irrigation Regimes Viz. Ethylene-Diamine-Tetraacetic Acid, Peracetic Acid, Etidronic Acid, Distilled Water On The Push-Out Bond Strength Of Various Resin Based Sealers Like Adseal, Dia-Proseal, Ep - Jaiswal, Shreeya; Varghese, Rana K; Singh, Raunak; Damodhar, Ippar Priyanka; Dubey, Astha; Shridhar, Chawre Rashi (Journal of Neonatal Surgery, 2025)
Aim: This study aims for comparative evaluation of the efficacy of EDTA, PAA, HEBP, Distilled water on push-out bond strength of Resin based sealers at three different root levels of endodontically treated mandibular premolars. Materials and methods: The study utilized 100 freshly extracted mandibular single-rooted premolars collected from patients aged 20–45 years through the Department of Oral and Maxillofacial Surgery and dental outreach camps of New Horizon Dental College and Research Institute, Bilaspur. Teeth extracted for orthodontic reasons and meeting inclusion criteria—single canals, intact apices, no caries, cracks, restorations, or severe anatomic variations—were cleaned and stored in normal saline. After decoronation at the cementoenamel junction to standardize length to 15 mm, access cavities were prepared, and working lengths were determined using an apex locator. Root canal instrumentation was carried out using Protaper Universal rotary files up to size F3. Results: The current study revealed a significant impact by the chemicals contained in irrigating solutions on bond strength to dentine in a push-out test of an epoxy resin sealer. Furthermore, sealing ability and bond strength strongly correlated with each other. Conclusion: Mandibular premolars were tested in this study to evaluate the Push-Out Bond Strength of various sealers. AH Plus sealer, regarded as the gold standard, consistently showed superior bond strength across all root levels. Epoxy sealers outperformed Adseal, Dia-Proseal, and RC Seal in this aspect. Among the irrigation agents, EDTA and HEBP demonstrated significantly higher bond strength compared to PAA and distilled water, with AH Plus consistently exhibiting better performance than all other sealers. Notably, AH Plus showed the highest bond strength at the apical third, followed by the coronal and then the middle third. In contrast, EpoxySeal, Adseal, Dia-Proseal, and RC Seal displayed the highest bond strength at the apical third, followed by the middle and least at the coronal third. These findings highlight the superior efficacy of EDTA and HEBP, particularly in enhancing the apical bond strength of AH Plus, suggesting the need for further long-term clinical studies using similar irrigation protocols and sealers to confirm these results